A Sketch of the Great Agi.tater - (:unkn) unknown (McLean, Thomas, 1829)
Scholarly notes may be added at a later date.
1 print : col.
Keywords: Caricatures; Cartoons; Potatoes; O'Connell, Daniel, 1775-1847; Ireland -- Politics and government -- 1800-1837; Catholic emancipation